All Days 2016
DOI: 10.2118/182037-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Oil Displacement During Polymer Flooding in Porous Media with Micro-Inhomogeneities

Abstract: Enhanced oil recovery (EOR) process selection is an important part of field development strategy. One of the most important categories of EOR methods utilize certain chemical components that enhance the fluid properties. Polymer-enhanced waterfloods are one of the examples. During conventional waterfloods, the flow characteristics and displacement efficiency usually depends on a certain rock type in study. In a chemical EOR flood, there are a large number of parameters needed to be defined and optimized that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…So far, the transformation ( 16) is purely formal and has no physical sense, but it can help to reduce the number of effective components. Indeed, let us consider the phase transitions in the narrow pressure range, when the mixture with overall composition The problem is to find the matrix i   , which provides as many approximations like (19) as possible. Here is the mathematical procedure for the construction of this matrix.…”
Section: Modeling Of Gas-condensate Mixtures By Density Functional Hy...mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the transformation ( 16) is purely formal and has no physical sense, but it can help to reduce the number of effective components. Indeed, let us consider the phase transitions in the narrow pressure range, when the mixture with overall composition The problem is to find the matrix i   , which provides as many approximations like (19) as possible. Here is the mathematical procedure for the construction of this matrix.…”
Section: Modeling Of Gas-condensate Mixtures By Density Functional Hy...mentioning
confidence: 99%
“…In previous publications it has been demonstrated that various multiphase compositional problems can be modeled in the frame of the density functional hydrodynamics (DFH) [7][8][9][10][11][12][13][14][15][16][17], including practical digital rock applications [18][19][20][21][22][23][24][25][26]. In the present work we discuss the pore-scale modeling of gas-condensate mixtures in digital rock models obtained by X-ray microCT.…”
Section: Introductionmentioning
confidence: 99%